PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 009 BATURIJAL HILIR KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Jesika, Domi Adrian; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the lack of teachers in the use of mastery learning model IPS. As for the teachers who often do just conventional learning so that learning becomes menoton and students do not have the ability to discuss, motivated and ultimately affect learning outcomes. Based on the problems it is necessary to find a way to solve those problems. Among them are applying the quantum model of teaching that is more attractive to the environmental conditions of students in everyday life. Quantum teaching models provide an opportunity for students to learn with a nice atmosphere. In accordance with the concept of quantum teaching that